1995
DOI: 10.2172/122285
|View full text |Cite
|
Sign up to set email alerts
|

Water supply at Los Alamos during 1993. Progress report

Abstract: I ICover illustration: The graph illustrates the changes in water levels observed in the test welki in the main aquifer of the Los Alamos area. These changes indicate declines of as much as 35 feet. Water level changes in pumping well fields are discussed in Section V of this report. An Afirmative Acfion/Equal Opportunity Employer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…More than 50 active and inactive water‐supply and test wells intersect regional groundwater across the Pajarito Plateau (Griggs, 1955, 1964; Cushman, 1965; Cooper et al, 1965; Purtymun et al, 1990, 1995a, 1995b; Purtymun, 1995; Stoker et al, 1992; McLin et al, 1996, 1998; John Shoemaker, Inc., 1999; Koch and Rogers, 2003). Depth to water is greatest at mesa‐top locations in the western part of the plateau (e.g., 375 m, 1245 ft, at Well CdV‐R‐15‐3) and decreases eastward.…”
Section: Geologic Setting Of Groundwater Occurrencesmentioning
confidence: 99%
“…More than 50 active and inactive water‐supply and test wells intersect regional groundwater across the Pajarito Plateau (Griggs, 1955, 1964; Cushman, 1965; Cooper et al, 1965; Purtymun et al, 1990, 1995a, 1995b; Purtymun, 1995; Stoker et al, 1992; McLin et al, 1996, 1998; John Shoemaker, Inc., 1999; Koch and Rogers, 2003). Depth to water is greatest at mesa‐top locations in the western part of the plateau (e.g., 375 m, 1245 ft, at Well CdV‐R‐15‐3) and decreases eastward.…”
Section: Geologic Setting Of Groundwater Occurrencesmentioning
confidence: 99%
“…Both the Santa Fe Group and the Puye Formation are, at least locally, strongly anisotropic. Relatively short‐term pumping tests have confirmed that permeability normal to bedding is much lower than permeability parallel to bedding, both on the Pajarito Plateau (McLin et al, 2003; Purtymun et al, 1990, 1995b; Stoker et al, 1989) and elsewhere in the basin (Hearne, 1980). Estimates of anisotropy vary from 0.00005 (Hearne, 1980, pumping test analysis) to 0.04 (Hearne, 1980, hydraulic gradient analysis), to 0.01 (McAda and Wasiolek, 1988).…”
Section: Hydrogeologic Settingmentioning
confidence: 99%
“…Recent drilling has confirmed existence of water table conditions at many locations beneath the plateau. Pumping tests from water supply wells drilled to a depth of 609.6 m (2000 ft) below the water table have suggested that the deeper portions of the aquifer behave as “leaky confined.” Several estimates of specific storage ( S s ) have been derived from various pumping tests: 10 −4.8 m −1 in the Los Alamos Canyon well field (Theis and Conover, 1962) and 10 −5.5 and 10 −3.8 m −1 in the Otowi well field (Purtymun et al, 1990, 1995b). In the Los Alamos Canyon well field, Theis and Conover (1962) expanded on the “leaky confined” interpretation by stating that there are, in fact, several aquifers and several semiconfining beds in this well field.…”
Section: Hydrogeologic Settingmentioning
confidence: 99%
“…(3) (4) ESH-18 published a compilation report of borehole and well completion records (Purtymun 1995). This includes an inventory of wells and borings drilled through 1992.…”
Section: Compliance Summarymentioning
confidence: 99%
“…no major depletion of the resource as a result of pumping for the Los Alamos water supply (Purtymun 1995b). in shallow alluvial perched groundwater in Mortandad Canyon (downstream from the NPDES-permitted outfall for the radioactive waste treatment facility at TA-50) are depicted in Figure 5-6.…”
Section: Nonradioactive Constituents In Alluvial Groundwater Alluviamentioning
confidence: 99%